The Problem of Transworld Identity: in Defence of Essentialism. - Gricius, Pranciškus (Problems / Problemos, 2021)
In this article, the problem of transworld identity -- that is the question, if and how it is possible to ground the intuition that the same individual exists in more than one possible world -- is solved by arguing that individuals have essences. First of all, it is claimed that the concept of transworld identity is desirable since it betters both global pan-essentialism and counterpart theory. Then, necessary terminology for successful understanding of the transworld identity problem is introduced. Afterwards, it is contended that the well-known Chisholm's paradox for transworld identity can be resolved by appealing to individual essences. It is argued that if extreme haecceitism is true, then essences of individuals are non-qualitative and hence haecceitist switches are ontologically grounded. On the other hand, if reductionism is true, then essences of individuals are qualitative and hence haecceitist switches are impossible. Finally, it is shown that by referring to individual essences across possible worlds it is possible to solve the problem of cross-world identification.